Dependência sintática e processos morfofonêmicos (Revista de Estudos da Linguagem, 1996)
This study deals with the Sândi phenomena as a mot!vated and a variable role. It focuses the relationship between the syntactic dimension and the morphophonological system Df the Portuguese language. The data show that a strong syntactic dependence decreases the probability of loss of segments in the boundary of the words.